Cambio de matriz energética en Ecuador - Rivadeneira Vallejo, Milton (2023)
Ecuador oil producer, has focused its activities on it, the biggest consumere of oil are fleet, households consuming LPG liquefied petroleum gas for cooking and thermoelectric generatore. The change in energy mix expected to start in 2016, aims to strategically change the habits of non-renewable energy consumption to renewable energy, by: a) intensively generate hydroelectricity and other renewable energy sources, b) incorporating the transport based on electricity c) replace the use of gas by domestic induction cookers d) promote best practices for energy efficiency uses.